The neuroexistentialism of social connectedness and loneliness - Faraji, Jamshid; Metz, Gerlinde A. S. (Frontiers in Behavioral Neuroscience, 2025)
Social isolation and loneliness have been subject to extensive investigation and discussion by both modern neuroscience and existentialist philosophy. Neuroexistentialism, though controversial, examines how neuroscientific findings inform human existential concerns. In the present discussion, we argue that (1) in the absence of meaningful attributes, typically provided by relationships with objects and others, social isolation and loneliness lead an individual to a pervasive fear of being or the perception of “being-in-the-empty-world” which resembles an existential horror of loneliness; and (2) the pervasiveness of these influences justifies the ubiquity of cerebral responses to both objective and subjective prolonged social disengagement in humans. We also contend that current neuroscientific models of social behaviors, especially within social neuroscience, need to avoid self-affirmative and tautological notions to explain the originality of social connections in human life. By adopting a more integrative and critical approach, these models can better address the complex interplay between social disengagement and their neurological correlates known as the “social brain.” This can be accomplished through the establishment of a novel conceptual framework in modern neuroscience to remodel the triad of brain, solitary mind, and society.